Hepatic BRD4 Is Upregulated in Liver Fibrosis of Various Etiologies and Positively Correlated to Fibrotic Severity - Wu, Cichun; Cheng, Da; Peng, Yanghui; Li, Ying; Fu, Chunyan; Wang, Ying; Fu, Lei; Peng, Shifang; Ni, Xin (Frontiers in Medicine, 2021)
Bromodomain-containing protein 4 (BRD4) has been implicated to play a regulatory role in fibrogenic gene expression in animal models of liver fibrosis. The potential role of BRD4 in liver fibrosis in humans remains unclear. We sought to investigate the expression and cellular localization of BRD4 in fibrotic liver tissues. Human liver tissues were collected from healthy individuals and patients with liver fibrosis of various etiologies. RNA-seq showed that hepatic BRD4 mRNA was elevated in patients with liver fibrosis compared with that in healthy controls. Subsequent multiple manipulations such as western blotting, real-time quantitative polymerase chain reaction, and dual immunofluorescence analysis confirmed the abnormal elevation of the BRD4 expression in liver fibrosis of various etiologies compared to healthy controls. BRD4 expression was positively correlated with the severity of liver fibrosis, and also correlated with the serum levels of aspartate aminotransferase and total bilirubin. Moreover, the expression of C-X-C motif chemokine ligand 6 (CXCL6), a factor interplayed with BRD4, was increased in hepatic tissues of the patients with liver fibrosis. Its expression level was positively correlated with BRD4 level. BRD4 is up-regulated in liver fibrosis, regardless of etiology, and its increased expression is positively correlated with higher degrees of liver fibrosis. Our data indicate that BRD4 play a critical role in the progress of liver fibrosis, and it holds promise as a potential target for intervention of liver fibrosis.